Psychiatry - Gelder, Michael G.
This thoroughly revised new edition of Psychiatry, An Oxford Core Text, introduces the subject to the medical student in a concise, innovative and memorable way. Praised by lecturers and students alike for making even the most esoteric aspects of psychiatry accessible, this book will also appeal to social work and clinical psychology students, general practitioners and clinicians and health workers who see patients with psychiatric problems in the course of their practice. The book covers the most important psychiatric problems and includes a comprehensive coverage of signs, symptoms and diagnosis, assessment, aetiology, and psychiatry and the law. The book has been thoroughly revised and updated for this edition, and is in line with GMC guidelines on the teaching of psychiatry. The revised user-friendly, accessible text design is in response to student feedback. New material includes chapters which bring together somatoform and dissociative disorders, and disorders of eating and sleeping